Multiwavelength monitoring and reverberation mapping of a changing look event in the Seyfert galaxy NGC 3516. Issue 1 (22nd April 2021) - Oknyansky, V L; Brotherton, M S; Tsygankov, S S; Dodin, A V; Bao, D-W; Zhao, B-X; Du, P; Burlak, M A; Ikonnikova, N P; Tatarnikov, A M; Belinski, A A; Fedoteva, A A; et al.
ABSTRACT: We present the results of photometric and spectroscopic monitoring campaigns of the changing look AGN NGC 3516 carried out in 2018 to 2020 covering the wavelength range from the X-ray to the optical. The facilities included the telescopes of the CMO SAI MSU, the 2.3-m WIRO telescope, and the XRT and UVOT of Swift . We found that NGC 3516 brightened to a high state and could be classified as Sy1.5 during the late spring of 2020. We have measured time delays in the responses of the Balmer and He ii λ4686 lines to continuum variations. In the case of the best-characterized broad H β line, the delay to continuum variability is about 17 d in the blue wing and is clearly shorter, 9 d, in the red, which is suggestive of inflow. As the broad lines strengthened, the blue side came to dominate the Balmer lines, resulting in very asymmetric profiles with blueshifted peaks during this high state. During the outburst the X-ray flux reached its maximum on 2020 April 1 and it was the highest value ever observed for NGC 3516 by the Swift observatory. The X-ray hard photon index became softer, ∼1.8 in the maximum on 2020 April 21 compared to the mean ∼0.7 during earlier epochs before 2020. We have found that the UV and optical variations correlated well (with a small time delay of 1–2 d) with the X-ray until the beginning of 2020 April, but later, until the end of 2020 June, these variations were not correlated. We suggest that this fact may be a consequence of partial obscuration by Compton-thick clouds crossing the line of sight.